Pentingnya Menjaga Kesehatan Organ Reproduksi Pada Remaja di SMA Negeri 22 Maluku Tengah - Dewi Arwini Bugis; Sakina Makatita (BADAN PENERBIT STIEPARI PRESS, 2023)
. Lack of knowledge and information about sex, as well as wrong perceptions about aspects of sexuality, is one indicator of increased free sex behavior among adolescents. The purpose of this community service is to provide early adolescents with knowledge about reproductive health in adolescents. The method used includes the design and manufacture of community service practice materials as well as material counseling on adolescent reproductive health. The results of the service show that the participants' knowledge is high after being given counseling material, namely 85,4%. In addition, based on oral evaluations, 80% of the participants were able to re-explain the definition of adolescent reproductive health, how to protect the reproductive organs, reproductive organ infections, and HIV-AIDS. It is recommended that schools cooperate with health centers in providing information about adolescent reproductive health